2011
DOI: 10.1097/acm.0b013e31822631b3
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Development of Clinical Reasoning Ability Across Five Medical Schools Using a Progress Test

Abstract: Years of training accounted for most of the variation in DPR and CDI performance. As a rule, students at higher training levels performed better on both tests, though the expected larger gains during the third year of medical school did not materialize.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 11 publications
0
24
0
2
Order By: Relevance
“…In support of this claim, our results echoed a cross-sectional multi-institutional study that investigated differences in clinical reasoning skills of undergraduate medical students. In this study, Williams et al 21 reported clinical data interpretation gains at each level of undergraduate medical training, though gains in the 3rd year were not as substantial. They also reported that medical school elements (e.g., curriculum, instructional delivery systems, faculty, etc.)…”
Section: Item Difficulty and Item Type Analysismentioning
confidence: 86%
“…In support of this claim, our results echoed a cross-sectional multi-institutional study that investigated differences in clinical reasoning skills of undergraduate medical students. In this study, Williams et al 21 reported clinical data interpretation gains at each level of undergraduate medical training, though gains in the 3rd year were not as substantial. They also reported that medical school elements (e.g., curriculum, instructional delivery systems, faculty, etc.)…”
Section: Item Difficulty and Item Type Analysismentioning
confidence: 86%
“…Williams and colleagues 26 reported that the clinical reasoning ability of students from five medical schools did not increase during third-year clerkships despite significant improvement in years one and two. As Prince and colleagues 27 found, one may argue that students have difficulty in applying medical knowledge to real clinical practice because they do not have sufficient basic science knowledge.…”
Section: Discussionmentioning
confidence: 97%
“…items should test knowledge that is specific to the specialty of medicine, test ready knowledge (knowledge required as a prerequisite to function in a practical situation), be important knowledge which is required for the successful practice of medicine, have a practical relevance for the successful handling of high-prevalence or high-risk medical situations, and the knowledge should form the basis of one or more important concepts of the curriculum''. Progress tests provide a unique opportunity for assessing growth in students' knowledge (Williams et al 2011), and can provide data on which to base decisions about the curriculum as a whole as well as remediation strategies for the individual student. To accomplish these goals, however, requires significant investment of faculty and administrative time to develop item banks and ensure that exams remain relevant.…”
Section: Assessing Integrationmentioning
confidence: 99%